Phytochemical analysis and anti-inflammatory activity of Cladophora aegagropila extract - Aleksandra Aleksandrova; Mariia Nesterkina; Svitlana Gvozdii; Iryna Kravchenko (Shahrekord University of Medical Sciences, 2020)
Introduction: The aim of this research is centered on phytochemical analysis and anti-inflammatory activity of Cladophora aegagropila extract. Methods: Total flavonoid content in the appropriate ethanol extract of C. aegagropila was determined using the spectrometric method. Anti-inflammatory activity was evaluated by the models of carrageenan-induced and allyl isothiocyanate-induced (AITC-induced) inflammation of hind limb in rats. Experimental animals were divided into 3 groups, 5 animals each: 1st group - control; the animals without therapy of induced inflammation, 2nd group - animals were treated with application of 5% ointment containing C. aegagropila; 3rd group - animals were treated with application of 5% ibuprofen. Evaluation of anti-inflammatory activity was performed by determination of dynamic change of thickness and volume of affected animal limb for carrageenan-induced inflammation for 8 days (with daily registration of records), and for AITC induced inflammation for 24 h (with registration of records after 30 min, 1 h, 2 h, 3 h, 6 h and 24 h since phlogogen was introduced). Results: Flavonoids content in C. aegagropila extract varied depending on ethanol concentration: usage of 40% ethanol led to 18.2 mg of flavonoid recovery on 1.0 g of dry raw material; 70% ethanol - 39.5 mg and 96% ethanol - 35.5 mg. Therapy of 5% ointment based on C. aegagropila extract decreased inflammatory response caused by the subplantar introduction of the corresponding phlogogen. Conclusion: The ointment from C. aegagropila extract shows anti-inflammatory activity by inhibiting inflammation caused by AITC and carrageenan.